0.15. Упростите выражение: 1) 2а - 3b - (4а + 7b + c + 3); 2) 2xy - y^2 + (у^2 - xy) -...

+876 голосов
218k просмотров

0.15. Упростите выражение: 1) 2а - 3b - (4а + 7b + c + 3); 2) 2xy - y^2 + (у^2 - xy) - (х^2+ ху); 3) (-2х^2 +х+ 1) - (х^2 - x+ 7) - (4х^2 + 2х + 8); 4) (3а^2 - a + 2) + (-3a^2 + За - 1) - (а^2 - 1); 5) (1 - x+ 4х^2 - 8х^3) + (2х^3 + x^2 - 6x - 3) - (5х^3 – 8х^2); 6) (0,5а - 0,6b + 5,5) - (-0,5а + 0,4b) + (1,3b - 4,5).


image

Алгебра | 218k просмотров
Дан 1 ответ
+199 голосов

Ответ:

Раскрываем скобки и приводим подобные слагаемые:

1)  2a-3b-4a-7b-c-3=-2a-10b-c-3;

2)  2xy-y^2+y^2-xy-x^2-xy=(2xy-xy-xy)-(y^2-y^2+y^2)=0-y^2=y^2;

3)  -2x^2+x+1-x^2+x-7-4x^2-2x-8= -2x^2-x^2-4x^2+x+x-2x+1-7-8= (-2x^2-x^2-4x^2)+2x-2x+1-15=-7x^2-14=-7(x^2-2);

Объяснение:

(536 баллов)